Clinical Evaluation of the First Automated Assay for the Detection of Stimulating TSH Receptor Autoantibodies - Allelein, S.; Ehlers, M.; Goretzki, S.; Hermsen, D.; Feldkamp, J.; Haase, M.; Dringenberg, T.; Schmid, C.; Hautzel, H.; Schott, M. (Hormone and Metabolic Research, 2016)
Until recently, stimulating TSH receptor autoantibodies (sTRAbs) could only be measured by bioassays. A new assay system, which directly detects sTRAb in sera by applying bridge technology, has been established and is now available as automated chemiluminescence (bridge) immunoassay. We evaluated the automated bridge assay in clinical routine and compared it with a conventional automated TRAb assay (competition assay). Altogether, 226 Graves’ disease (GD), 57 autoimmune thyroiditis, 74 non-autoimmune nodular goiter and 49 thyroid cancer patients, as well as 41 healthy controls were retrospectively evaluated. ROC plot analysis based on sera of newly diagnosed GD patients revealed an area under curve of 0.99 (95% CI: 0.99–1.0) indicating a high assay sensitivity and specificity. The highest sensitivity (100%) and specificity (99%) were seen at a cut-off level of 0.55 IU/l. The calculated positive predictive value was 94%, whereas the negative was 100%. Applying a ROC plot-derived cut-off of≥0.30 IU/l, derived from sera of GD patients already receiving antithyroid drug therapy for≤6 months, the sensitivity was 99% whereas the specificity was 98%. Detailed comparison of both assay systems used revealed a slightly different distribution of sTRAb and TRAb. Measurement of sTRAb during follow-up revealed a steady decline over one year of follow-up. In summary, our results demonstrate that the new automated bridge assay system for detecting sTRAb has a high sensitivity and specificity for diagnosing GD and to discriminate from other thyroid diseases, respectively. Our study, however, does not provide full evidence that the bridge assay is specific for sTRAb only.
Keywords: Graves’ disease; autoimmune thyroiditis; bridge assay